Patriarchy and Religion: The Relationship Between Muslim Youth Attitudes Towards Patriarchal Power and Their Religious Commitment - Mohammed, Aqeel Norri (2004)
This study aims to explain the relationship between patriarchy and religion. This relation was deduced from the literature of psychology, anthropology, sociology, religious writings and historical literatures related to patriarchy and religion. Patriarchy and religion are abstract variables and thus difficult to measure. The relationship between them is also abstract. As such this study derived operational variables to design measurable operational proposition. The variables are ‘patriarchal power’(PP) and ‘religious commitment’ (RC), while the operational proposition is “the relationship between Muslim youth attitudes towards patriarchal power and their religious commitment’. Smelser’s social action theory was used to derive both variables of the new proposition through design models of patriarchal social action and Islamic social action.This study used the operational variables’ definitions to construct scales of youth attitudes towards patriarchal power and youth religious commitment. The Likert method was used to construct both scales. Both of them were deemed successful according to the Likert method. Both scales were used to quantify the operational variables and then to quantify the relationship between both of them. This method provided feedback to understand the relationship between patriarchy and religion because the operational proposition was derived from the abstract one. The methodological approach of the field study used was analytic and descriptive while the method was sampling social survey. The stratified sample was chosen randomly. The unit of sampling was youth between 18-30 years old. Methodological instrument was questionnaire consisting of general information concerning socio cultural characteristics of the respondents and two scales, one for religious commitment and another for patriarchal power. Based on the results of T-test, regression and ANOVA, the main results of the field study can be summarized as follows: 1) This study showed an arithmetic mean of the respondents in RC scale of 178.21 while the standard deviation was 23.403. The hypothetical mean of the scale was 134 which was less than mean of the sample. The T–test value between both means was 42.236. It was significantly above than the 0.05 level.2) This study stated that the arithmetic mean of the respondents in PP scale was 79.61 while the standard deviation was 14.53. The study showed a hypothetical mean of 80 which is higher than mean of the sample. The T –test value between both means was – 0.599. It was not significant at the 0.05 level. 3) The study showed a significant relationship between RC and PP. So the operational proposition was significant in terms of the simple linear Regression test where Beta coefficient is 0.387, which is significantly higher than 0.0001 level. 4) The following results according to the hypotheses tested by the Univariate ANOVA tests: a) There are no significant differences between youth in their attitudes towards patriarchal power in terms of the interaction between their religious commitment levels and their gender, family background, inhabitancy area, family type, religious commitment of the fathers and parents educational levels. b) There are significant differences between youths in their attitudes towards patriarchal power in terms of the interaction between family type and religious commitment levels at 0.09 where the F value is 2.418. c) There are significant differences between youths in their attitudes towards patriarchal power in terms of the interaction between educational levels of fathers and their religious commitment levels at 0.08 where the F value is 1.604. d) There are significant differences between youths in their attitudes towards patriarchal power in terms of the interaction between family size and religious commitment levels at 0.005 where the F value is 3.753. The main conclusion of this study is that, there is positive relationship between patriarchy and religion in Arabian Muslim society. This result supports the assumption of some writers like Freud, Sharabi, Zieur, and Halim Barakat who emphasized the relationship between patriarchy and religion. But the researcher suspects that this relationship is decreasing because the Beta coefficient of the relationship between religious commitment and patriarchal power is not very high.